2010
DOI: 10.1016/j.neunet.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Approximating the stability region of a neural network with a general distribution of delays

Abstract: We investigate the linear stability of a neural network with distributed delay, where the neurons are identical. We examine the stability of a symmetrical equilibrium point via the analysis of the characteristic equation both when the connection matrix is symmetric and when it is not. We determine a mean delay and distribution independent stability region. We then illustrate a way of improving on this conservative result by approximating the true region of stability when the actual distribution is not known, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…(1.4) is stable near λ = d and Hopf bifurcation cannot occur. For a delayed differential equations with a Gamma distribution delay kernel, the effect of β and m on the stability and bifurcations of the equilibrium has been investigated [5,13]. However, when f (s) is given by Eq.…”
Section: Applications and Discussionmentioning
confidence: 99%
“…(1.4) is stable near λ = d and Hopf bifurcation cannot occur. For a delayed differential equations with a Gamma distribution delay kernel, the effect of β and m on the stability and bifurcations of the equilibrium has been investigated [5,13]. However, when f (s) is given by Eq.…”
Section: Applications and Discussionmentioning
confidence: 99%
“…This can be argued successfully, for example, in machining when the tool has nearly infinite stiffness perpendicular to the cutting direction [75], or in laser dynamics where light travels over a fixed distance [40]. On the other hand, in many contexts, including in biological systems and in control problems [9,10,11,21,36,38,68,82], the delays one encounters are not actually constant. In particular, they may depend on the state in a significant way, that is, change dynamically during the time-evolution of the system.…”
mentioning
confidence: 99%
“…13 Distributed delay models appear in a wide range of applications such as hematopoiesis, 14 population biology, [15][16][17] or neural networks. [18][19][20] Four-dimensional models that incorporate the positive self-regulation of glucocorticoid receptors (GR) in the pituitary have been investigated in previous studies. [21][22][23][24][25] In particular, in Kaslik and Neamtu, 25 we constructed a 4-dimensional general model with distributed time delays, which represents an extension of the minimal model of Vinther et al 9 In Gupta et al, 21 it has been suggested that positive self-regulation of GR may trigger bistability in the dynamical structure of the HPA model, ie, there exist 2 asymptotically stable equilibrium states: one corresponding to the normal disease-free state with higher cortisol levels and a second one with lower cortisol levels related to a diseased state associated with hypocortisolism.…”
Section: Introductionmentioning
confidence: 99%